Hypolipidemic Effects of Rosa Damascena Mill. Extract in Streptozotocin-induced Diabetic Rats - Tamam Jauhar; Bilqis Inayatillah; Maftuchah Rochmanti; Achmad Basori (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Diabetes mellitus is a chronic hyperglycemic condition with a lot of complication which canlead to death. Vascular complication in diabetes commonly caused by dyslipidemia which characterizedby decreased HDL, elevated LDL, Cholesterol and Triglyceride. Rosa damascena- an ornamental plantthoughts to have anti-hyperglycemia and antioxidant effects because of its large amount of polyphenoliccomponents . This study analyzed hypolipidemic activity properties of an ethanol extract of Rosa damascenaby measuring the lipid profile using various doses. Methods: This research is experimental study withrandomized post-test only control group design. Twenty male Wistar rats divided into 5 groups; The groupswere Healthy Control Group (HCG), Diabetes Group (DG), and Extract Group: P1 (250 mg/kgBW), P2(500 mg/kgBW), P3 (1000 mg/kgBW). All treatment groups were injected by single-dose streptozotocin50 mg/kgBW to induce diabetes, and given the Rosa damascena ethanolic extract oral treatment for 2weeks. Statistical results showed that Rosa damascena significantly decrease cholesterol (58.2±15.19), LDL(11±2.44) optimally in dose 250 mg/KgBW and triglyceride (96.7±44.2) optimally in dose 500 mg/kgBWafter 14 days. Conclusion: Rosa damascena extract seems to be great candidate for anti-hyperlipidemicdrugs.